Regulatory and Legal Bases of Applying Citizens Biometric Registration Technology in the Electoral Process of the Kyrgyz Republic - N. S. Chimarov (Евразийская интеграция: экономика, право, политика)
New technologies of voters’ biometric data registration evidence the election organizers’ desire to strengthen the democratic foundations of the citizens’ will and increase public confidence in electoral innovations related to the integration of modern achievements of the digital economy in the electoral process practice. In this regard, the question of applying the potential of the new economic order in the direction of rapid and more accurate determination of the true number of citizens with active suffrage naturally arises. Based on the above, it seems necessary to conduct a special research on the experience of several countries that have reached a particular result in the solution of the stated objectives and above all the experience of the Kyrgyz Republic in the sphere of legal fixation technology of citizens biometric registration.